Meal of cassava foliage as pigment of diets with cassava meal and oil of African oil palm for laying hens - Zacarias, J. B.; Valdivié, M.; Bicudo, Silvio José [UNESP] (My University, 2012)
Twenty-eight White Leghorn laying hens, of the Cuban commercial hybrid L-33, were used for eight weeks within the laying peak (36 to 43 weeks of age), to evaluate the meal of root of cassava (Manihot esculenta Crantz) and the crude oil of African oil palm (Elaeis guineensis J.) as pigments of the egg yolks, out of their incorporation to the diet of laying hens during the laying peak. The birds were allocated in individual cages, with 108 g of feed/bird/d, water ad libitum, and 16 h of light. Analysis of variance was performed, according to one-way design with two treatments and fourteen repetitions (one cage with one hen). The treatments consisted of two diets (I- cassava meal + African palm oil, II- cassava meal + African oil palm + 2.5 % of cassava foliage meal). The viability was of 100 % in all the treatments. No differences were found for laying (91.59 and 90.10 %), which surpassed the potential of this hybrid during the laying peak (90 %), feed conversion/egg (118 and 120 g of feed/egg), mass of egg produced (3071 and 3027 g/bird) and mass conversion (1.98 and 2.00). The pigmentation of the egg yolk was doubled, by adding 2.5 % of meal of cassava foliage to the diets (3 and 6 in the scale of Roche). It was likeable to enhance the pigmentation of the egg yolk and reduce the feeding costs of the laying hens, when including 2.5 % of meal of cassava foliage to diets where the cassava meal and the oil of the African oil palm are basic sources of starch and lipids for the laying hens.
Keywords: Cassava; Eggs; Pigmentation